Uso do estimulador de crescimento, inseticida e fungicida no tratamento de sementes de soja - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Glycine max soy (L.) is the most cultivated oilseed in the world. In Brazil, it is the culture with the highest growth, occupying approximately 36 thousand hectares of planted area. In addition, it is also highly affected by pests and highly harmful insects, especially in the early stage of the cycle, making the practice of seed treatment become necessary to give the plant defense conditions and to obtain a greater potential for this development. The objective of this work was to evaluate the effect of the seeds treatment with insecticide, fungicide and growth stimulator based on minerals, isolated and in mixture, on the germination of soybean seeds and their plantar development. Products tested were Fipronil Alta 250FS; Derosal Plus Bayer (CARBENDAZIM + TIRAM); Bio-x TSL Micro-Schist (N 5%, Mo 5%, Co 0.5%, Zn 0.5% COT 10%, Schist Extract where the seeds of Bayer BS 2606 were treated at doses of 0.2 (Germination speed index), aerial part length and root, aerial shoot and root dry mass and aging were evaluated after the treatment. The fungicide was efficient, provided a restorer effect and increased seed vigor. The amino acid did not present a beneficial effect except when combined with the fungicide. The interaction of the three products impaired the treatment, reduced the physiological quality of the seeds, decreased vigor and germination, especially in the accelerated aging test.
Keywords: Glycine max soy (L.); Efeito fitotônico; Envelhecimento acelerado; Sanidade de sementes; Tonic effect; Accelerated aging; Seed health; CNPQ::CIENCIAS EXATAS E DA TERRA